The Role of Biotechnology in the Development of Recombinant Drugs - Sattari Sobhani, Alaleh (Health Nexus, 2025)
Biotechnology has emerged as a cornerstone of modern pharmaceutical science, providing the foundation for the discovery, design, and production of recombinant drugs that have transformed global healthcare. This narrative review, using a descriptive analytical approach, explores the conceptual, industrial, and clinical dimensions of recombinant drug development. It begins by outlining the molecular foundations of biotechnology, emphasizing recombinant DNA technology, genetic manipulation, and expression systems that enable large-scale synthesis of therapeutic proteins. Industrial advancements in upstream and downstream processing, including cell line optimization, bioreactor engineering, purification, and formulation, are analyzed to illustrate how biotechnology has evolved into a highly controlled and efficient production platform. The study further examines the integration of automation, digitalization, and Good Manufacturing Practice (GMP) standards that ensure product safety, consistency, and regulatory compliance. Clinically, recombinant drugs have achieved remarkable success across multiple disciplines, including endocrinology, oncology, hematology, and immunology. Recombinant insulin, monoclonal antibodies, cytokines, and gene therapy products exemplify the therapeutic versatility of these biopharmaceuticals in managing both chronic and rare diseases. The review also highlights emerging applications in neurodegenerative and genetic disorders, where recombinant enzymes and CRISPR-mediated platforms are redefining the boundaries of precision medicine. Despite challenges related to production cost, ethical considerations, and equitable access, recombinant biotechnology continues to expand its impact through innovation and interdisciplinary collaboration. The findings underscore the role of biotechnology as a transformative force that bridges molecular biology and clinical application, offering solutions that enhance safety, specificity, and therapeutic efficacy. Ultimately, this study concludes that recombinant biotechnology represents not only a scientific revolution but also a paradigm of sustainable innovation, shaping the future of personalized and regenerative medicine.